IMPLEMENTASI PROJECT BASED LEARNING UNTUK MENGEKSPLORASI KEMAMPUAN COMPUTATIONAL THINKING MAHASISWA - Rizal Dian Azmi; Siti Khoiruli Ummah (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
Computational Thinking (CT) or Computational Thinking is indispensable in mathematics. Programming Language courses are expected to facilitate and develop students' CT skills. The Project Base Learning (PjBL) learning model is used to see students' CT abilities. The project carried out in this PjBL learning is the making of learning media using Matlab. The media produced by the students has met the aspects of fluency in use, script accuracy, and flowchart logic. Students' CT abilities are in good category from the aspects of abstraction, logarithmic thinking, debugging / evaluation, and generalization because they have met the percentage of achievement of 82%.